Allocation of resources for health care in COVID-19 pandemic times: integrative review - Karla Rona da Silva; Fernanda Gonçalves de Souza; Fátima Ferreira Roquete; Shirlei Moreira da Costa Faria; Bruno César Ferreira Peixoto; Adriane Vieira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze information on resource allocation in the context of the COVID-19 pandemic, published in indexed scientific journals, from December 2019 to March 2020. Methods: This is an integrative literature review, which took place in March 2020. All databases were investigated and studies were found only in MEDLINE. After applying the established criteria, six articles were selected. Results: It was evident that the allocation of resources is carried out as the demands emerge. The fragility in presenting scientific-methodological evidence that can guide decision makers for assertive allocation of available resources is highlighted. The results showed that studies on this subject are incipient and need to be expanded. Final considerations: The need for health organizations and area authorities to be better prepared for the proper use of available resources, with allocation based on scientific evidence and maximization of resources is indicated.